2013
DOI: 10.1007/s00436-013-3285-7
|View full text |Cite
|
Sign up to set email alerts
|

Serological Detection of Circulating Angiostrongylus vasorum Antigen- and Parasite-Specific Antibodies in Dogs from Poland

Abstract: Dogs infected with Angiostrongylus vasorum, a potentially lethal parasite living in the heart and pulmonary arteries, may present severe respiratory and neurological sings and coagulopathies. Its occurrence is increasingly reported from various European countries, but little is known about its presence in Poland. In this first large-scale survey, 3,345 sera from polish dogs attending veterinary clinics in different parts of Poland for various reasons were collected and tested by an ELISA for the detection of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 37 publications
3
43
3
Order By: Relevance
“…With 1.36 % of the examined dogs being positive in both ELISAs, the prevalence in Hungary is significantly higher than that found for Germany (Schnyder et al 2013a), Italy (Guardone et al 2013) or Poland (Schnyder et al 2013b), which were all between 0.3 and 0.5 % and all obtained using the same validated procedures. More than 4 % of the dogs were positive for specific antibodies against A. vasorum, indicating parasite exposure: these dogs may have been sampled during the first five weeks after an A. vasorum infection, when antigen detection is still negative, or the dogs were parasite-free but still antibody-positive after anthelmintic treatment or natural clearance of the infection (Schnyder et al 2013a).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…With 1.36 % of the examined dogs being positive in both ELISAs, the prevalence in Hungary is significantly higher than that found for Germany (Schnyder et al 2013a), Italy (Guardone et al 2013) or Poland (Schnyder et al 2013b), which were all between 0.3 and 0.5 % and all obtained using the same validated procedures. More than 4 % of the dogs were positive for specific antibodies against A. vasorum, indicating parasite exposure: these dogs may have been sampled during the first five weeks after an A. vasorum infection, when antigen detection is still negative, or the dogs were parasite-free but still antibody-positive after anthelmintic treatment or natural clearance of the infection (Schnyder et al 2013a).…”
Section: Discussionmentioning
confidence: 65%
“…the combination of both ELISAs, again confirmed their utility for mass screening of dog populations. In contrast to Poland, where testing of more than 3000 sera revealed for the first time the presence of A. vasorum in the country (Schnyder et al 2013b) and positive foxes were identified subsequently (Demiaszkiewicz et al 2014), the occurrence of A. vasorum in Hungary had already been reported. The parasite had first been described in foxes: 5 of 100 red foxes (Vulpes vulpes) from 16 Hungarian counties dissected in 2002 were positive at necropsy, with four foxes having low worm burdens (1 -7 adult specimens) and a single fox having a moderate worm burden (8 -14 specimens).…”
Section: Discussionmentioning
confidence: 93%
“…A number of factors infl uence the distribution of A. vasorum (Mor-gan et al, 2009). The parasite does not necessarily occur in large endemic areas, like Dirofi laria spp., but its presence is incoherent with hyperendemic foci surrounded by areas of low prevalence or localities with sporadic cases (Barutzki and Schaper, 2009;Guardone et al, 2013;Schnyder et al, 2013b). However, it is clear from recent studies that the geographic range of A. vasorum in Europe is changing and that the parasite has been identifi ed in new areas distant from the original endemic foci in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the parasite has also been diagnosed in dogs in the neighbouring countries Hungary (e.g. Majoros et al, 2010;Tolnai et al, 2015) and the Czech Republic (Hajnalová et al, 2014), and also during a serological survey in Poland (Schnyder et al, 2013b), a serological survey was performed to assess the current distribution of this parasitic infection in dogs from Slovakia.…”
Section: Introductionmentioning
confidence: 99%
“…In dog, distinct isolated endemic foci were reported during the last century in south-western France, Ireland, Switzerland, Southeast England and Wales, and Denmark. Canine angiostrongylosis is clearly emerging both in North America [6] and Europe [7] where it was recently further recorded in Greece [8], The Netherlands [9], different parts of Germany [10], Italy [11], Slovakia [12] Poland [13] and Hungary [14]. In temperate Western Europe climatic conditions are highly suitable to the completion of Angiostrongylus vasorum life cycle and Belgium is part of a vast area characterized by its high predicted suitability for parasite transmission [15].…”
Section: Introductionmentioning
confidence: 99%